PPARG Modulated Lipid Accumulation in Dairy GMEC via Regulation of ADRP Gene. Issue 1 (January 2015) - Kang, Yu; Hengbo, Shi; Jun, Luo; Jun, Li; Wangsheng, Zhao; Huibin, Tian; Huaiping, Shi
ABSTRACT Peroxisome proliferator‐activated receptor‐gamma (PPARG) is considered to be a central regulator of lipid metabolism in mammary cells. Adipose differentiation‐related protein (ADRP), a member of PAT family (Perilipin, ADRP, TIP47 family), plays a key role in lipid accumulation in mammary gland. It has been found that PPARG significantly promoted lipid storage in goat mammary epithelial cells (GMEC), which was abolished after knockdown of ADRP gene. The results of real‐time PCR, Western blot and luciferase reporter assay for goat ADRP promoter showed that ligand‐activated PPARG up‐regulated the ADRP gene expression and activity of ADRP promoter. Moreover, PPARG directly interacted with a PPRE (PPAR response element) spanning at −1003 to −990 on ADRP promoter. In this study, to our knowledge, we are the first to verify the function of PPARG on lipid storage on cellular level of goat mammary gland and our results revealed a novel pathway that PPARG may regulate lipid accumulation by controlling the expression of ADRP gene. J. Cell. Biochem. 116: 192–201, 2015. © 2014 Wiley Periodicals, Inc.